A low-surface-energy antifouling coating with degradable performance and a preparation method and application thereof
Patent Information
- Application Number
- CN202510098543.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-01-22
AI Technical Summary
然而,传统的防污涂层通常含有大量的防污剂,当防污剂释放到海洋环境中时,杀死污损生物的同时严重危害海洋生态系统,造成二次污染
[0033] (1) The present invention polymerizes epoxy containing ester group segments with low surface energy siloxane with amino group, and uses the ring-opening reaction of amino and epoxy to graft ester group onto the side chain of siloxane polymer, thereby achieving the synergy of degradability and low surface energy, and further providing degradability for antifouling coating.
Smart Images

Figure CN119931496B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of marine antifouling coating technology, and in particular to a low surface energy antifouling coating with degradable properties, its preparation method, and its application. Background Technology
[0002] Marine biofouling is the undesirable accumulation of marine microorganisms, plants, and animals on the surface of underwater structures submerged in seawater, causing significant damage to marine vessel facilities and marine resources. Among numerous antifouling strategies, the application of marine antifouling coatings is the simplest, most economical, and most effective method. However, traditional antifouling coatings typically contain large amounts of antifouling agents. When these agents are released into the marine environment, they kill fouling organisms and severely harm the marine ecosystem, causing secondary pollution.
[0003] Low surface energy antifouling coatings are marine antifouling coatings that do not release antifouling agents. They are typically based on organosilicon or organofluorine polymers and have the advantages of structural stability and non-hydrolysis. Polydimethylsiloxane (PDMS) coatings are widely used as environmentally friendly antifouling coatings due to their significant characteristics such as low surface energy, low Young's modulus, and cost-effectiveness.
[0004] Biodegradable antifouling coatings are a class of antifouling materials with biodegradable ester groups. Their biodegradability comes from the ester groups in the side groups, which break down when washed by water flow, forming a self-renewing surface and improving antifouling performance. Therefore, combining low surface energy antifouling with biodegradable antifouling has become an urgent problem to be solved. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a low surface energy antifouling coating with degradable properties, its preparation method, and its application. In this invention, epoxy containing ester segments is polymerized with low surface energy siloxane containing amino groups, which can achieve dual antifouling. Furthermore, the introduction of epoxy groups improves the mechanical properties of the coating. While enhancing antifouling performance, this combination method can also avoid the potential pollution of the marine environment by polymer materials.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a low surface energy antifouling coating with degradable properties, characterized in that the structure of the low surface energy antifouling coating comprises an amino group of bis(3-aminopropyl)-terminated polydimethylsiloxane linked to an epoxy group of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester.
[0008] Preferably, the connecting chemical bond includes an ester bond.
[0009] In a second aspect, the present invention provides a method for preparing a low surface energy antifouling coating with degradable properties according to the first aspect, the method comprising:
[0010] The mixture was prepared by mixing bis(3-aminopropyl)-terminated polydimethylsiloxane and 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester and then curing the mixture.
[0011] In this invention, a one-pot polymerization method is used, in which the epoxy groups are opened by the polymerization reaction of NH2-PDMS with 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester, and the ester groups are grafted onto the low surface energy siloxane side chains. The specific structure is as follows. Figure 1 As shown, its biodegradability originates from the ester groups in the side groups. In water, these groups are broken down by water flow, forming a self-renewing surface and improving antifouling performance. Therefore, combining low surface energy antifouling with biodegradable antifouling can effectively compensate for their respective shortcomings, thereby enhancing the overall antifouling performance of the antifouling coating.
[0012] Preferably, the molar ratio of the amino group of the bis(3-aminopropyl)-terminated polydimethylsiloxane to the epoxy group of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is 1:(1-5), and the (1-5) can be, for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5.
[0013] In this invention, within the above molar ratio range, 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is fully connected with bis-3-aminopropyl-terminated polydimethylsiloxane, significantly improving the overall antifouling performance of the antifouling coating.
[0014] Preferably, the molecular weight of the bis(3-aminopropyl)-terminated polydimethylsiloxane is 2500-3000. For example, it can be 2000, 2050, 2100, 2150, 2200, 2250, 2300, 2350, 2400, 2450 or 2500, etc.
[0015] Preferably, the preparation method further includes adding a solvent to the mixed raw materials and stirring, and then condensing and refluxing in an oil bath.
[0016] Preferably, the solvent includes any one or a combination of at least two of tetrahydrofuran, ethyl acetate, or acetone.
[0017] Preferably, the stirring time is 20-40 minutes, and the stirring speed is 100-500 rpm. The 20-40 minutes can be, for example, 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes, 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes, or 40 minutes. The 100-500 rpm can be, for example, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, or 500 rpm.
[0018] Preferably, the temperature of the oil bath is 75-85℃, for example, it can be 75℃, 76℃, 77℃, 78℃, 79℃, 80℃, 81℃, 82℃, 83℃, 84℃ or 85℃, etc.
[0019] Preferably, the condensation reflux time is 20-24 hours, for example, it can be 20 hours, 21 hours, 22 hours, 23 hours or 24 hours.
[0020] Preferably, the curing time is 3-7 days, for example, 3 days, 4 days, 5 days, 6 days or 7 days.
[0021] Preferably, the curing temperature is 20-30℃, for example, it can be 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃ or 30℃, etc.
[0022] Preferably, the preparation method further includes immersing the cured coating in silicone oil.
[0023] In this invention, the cured coating is immersed in silicone oil to form an ultra-slippery antifouling surface, thereby obtaining a smooth and relatively new coating surface that will not cause high molecular pollution to the ocean, and ultimately achieves excellent marine antifouling effect.
[0024] Preferably, the silicone oil includes any one or a combination of at least two of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, or fluorinated silicone oil.
[0025] Preferably, the viscosity of the silicone oil is 5-100 mPa·s, for example, it can be 5 mPa·s, 10 mPa·s, 20 mPa·s, 40 mPa·s, 60 mPa·s, 80 mPa·s or 100 mPa·s, etc.
[0026] Preferably, the soaking time is 3-7 days, for example, 3 days, 4 days, 5 days, 6 days or 7 days.
[0027] In this invention, an immersion experiment is conducted to investigate the degradability of the coating. The steps of the immersion experiment include immersing the coating in artificial seawater, drying the residual moisture on its surface, and re-weighing the coating to determine its degradability.
[0028] Preferably, the coating is immersed in artificial seawater for 30-120 days, for example, 30 days, 40 days, 60 days, 80 days, 100 days or 120 days.
[0029] Preferably, the mass ratio of the coating to the artificial seawater is 1:(100-200). The (100-200) can be, for example, 100, 120, 140, 160, 180, or 200.
[0030] Preferably, the temperature at which the moisture on the surface of the drying coating is dried is 55-65°C. The 55-65°C can be, for example, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, or 65°C.
[0031] Thirdly, the present invention provides an application of the low surface energy antifouling coating with biodegradable properties described in the first aspect in the treatment of marine biofouling.
[0032] Compared with the prior art, the present invention has at least the following beneficial effects:
[0033] (1) The present invention polymerizes epoxy containing ester group segments with low surface energy siloxane with amino group, and uses the ring-opening reaction of amino and epoxy to graft ester group onto the side chain of siloxane polymer, thereby achieving the synergy of degradability and low surface energy, and further providing degradability for antifouling coating.
[0034] (2) This invention has excellent smoothness, environmental friendliness and biodegradability, and the super-smooth surface itself has antifouling properties. The preparation process is simple, retains the excellent smoothness of the super-smooth surface, and its low surface energy significantly reduces the adhesion of marine organisms to the surface.
[0035] (3) The coating studied can also form a super-slippery antifouling surface by injecting silicone oil, thereby obtaining a smooth and relatively new coating surface that will not cause high molecular pollution to the ocean, ultimately achieving excellent marine antifouling effect. The addition of epoxy groups improves the mechanical properties of the coating, achieving a synergistic effect of multiple antifouling effects. Attached Figure Description
[0036] Figure 1 This is a schematic diagram of the molecular formula of a low surface energy antifouling coating substrate with biodegradable properties.
[0037] Figure 2The image shows a scanning electron microscope schematic diagram of a low surface energy antifouling coating substrate with biodegradable properties. In the diagram, A is the coating surface of Example 4, B is the coating cross-section of Example 4, C is the coating surface of Example 1, and D is the coating cross-section of Example 1.
[0038] Figure 3 This is a schematic diagram of the infrared spectrum of the flocculent material obtained after soaking in artificial seawater in Example 1.
[0039] Figure 4 Schematic diagram of the antibacterial effect of low surface energy antifouling coating with degradable properties, wherein Figure A is the result of blank sample, Figure B is the result of Example 1, Figure C is the result of Example 2, Figure D is the result of Example 3, Figure E is the result of Example 4, Figure F is the result of Example 5, Figure G is the result of Example 6, Figure H is the result of Comparative Example 1, Figure I is the result of Comparative Example 2, and Figure J is the result of Comparative Example 3. Detailed Implementation
[0040] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.
[0041] Example 1
[0042] This embodiment prepares a low surface energy antifouling coating with biodegradable properties.
[0043] 2.5g of bis(3-aminopropyl)-terminated polydimethylsiloxane (molecular weight 2500) and 0.15g of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester were mixed at a functional group molar ratio of 1:1. 10g of tetrahydrofuran solvent was added, and the mixture was stirred for 30 minutes until the oily liquid was completely dissolved at a speed of 300 rpm. The mixture was then transferred to a flask and stirred and refluxed in an oil bath at 80°C for 20 hours. After the reaction was completed, the viscous liquid was transferred to a rigid polytetrafluoroethylene mold (mold size 15*15*2mm) and dried and cured at 25°C for 3 days.
[0044] The cured coating was immersed in 10g of dimethyl silicone oil with a viscosity of 100mPa·s for 3 days to swell. After 3 days, the coating was removed and any residual silicone oil adhering to the surface was cleaned off.
[0045] Example 2
[0046] This embodiment prepares a low surface energy antifouling coating with biodegradable properties.
[0047] 2.5g of bis(3-aminopropyl)-terminated polydimethylsiloxane (molecular weight 2500) and 0.45g of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester were mixed at a functional group molar ratio of 1:3. 10g of tetrahydrofuran solvent was added, and the mixture was stirred for 30 minutes until the oily liquid was completely dissolved at 300 rpm. The mixture was then transferred to a flask and stirred and refluxed in an oil bath at 80°C for 20 hours. After the reaction was completed, the viscous liquid was transferred to a rigid polytetrafluoroethylene mold (mold size 15*15*2mm) and dried and cured at 25°C for 3 days.
[0048] The cured coating was immersed in 10g of dimethyl silicone oil with a viscosity of 100mPa·s for 3 days to swell. After 3 days, the coating was removed and any residual silicone oil adhering to the surface was cleaned off.
[0049] Example 3
[0050] This embodiment prepares a low surface energy antifouling coating with biodegradable properties.
[0051] 2.5g of bis(3-aminopropyl)-terminated polydimethylsiloxane (molecular weight 2500) and 0.75g of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester were mixed at a functional group molar ratio of 1:5. 10g of tetrahydrofuran solvent was added, and the mixture was stirred for 20 minutes until the oily liquid was completely dissolved at a speed of 500 rpm. The mixture was then transferred to a flask and stirred and refluxed in an oil bath at 75°C for 24 hours. After the reaction was completed, the viscous liquid was transferred to a rigid polytetrafluoroethylene mold (mold size 15*15*2mm) and dried and cured at 30°C for 5 days.
[0052] The cured coating was immersed in 10g of dimethyl silicone oil with a viscosity of 50mPa·s for 7 days to swell. After 7 days, the coating was removed and any residual silicone oil adhering to the surface was cleaned.
[0053] Example 4
[0054] This embodiment prepares a low surface energy antifouling coating with degradable properties. The only difference between this embodiment and Example 1 is that the prepared coating is not immersed in silicone oil. Otherwise, it is the same as Example 1.
[0055] Example 5
[0056] This embodiment prepares a low surface energy antifouling coating with biodegradable properties. The only difference between this embodiment and Example 1 is that the mass of bis(3-aminopropyl)-terminated polydimethylsiloxane (molecular weight 2500) is 2.5 g, and the mass of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is 0.1 g. That is, the molar ratio of the functional groups of bis(3-aminopropyl)-terminated polydimethylsiloxane and 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is 1:0.6. All other aspects are the same as in Example 1.
[0057] Example 6
[0058] This embodiment prepares a low surface energy antifouling coating with degradable properties. The only difference between this embodiment and Example 1 is that the mass of bis(3-aminopropyl)-terminated polydimethylsiloxane (molecular weight 2500) is 2.5 g, and the mass of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is 1.4 g, that is, the molar ratio of the functional groups of bis(3-aminopropyl)-terminated polydimethylsiloxane and 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is 1:7. All other aspects are the same as in Example 1.
[0059] Comparative Example 1
[0060] This comparative example prepares a low surface energy antifouling coating with degradable properties. The only difference between this example and Example 1 is that epoxy resin E44 is used instead of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester. All other aspects are the same as in Example 1.
[0061] Comparative Example 2
[0062] This comparative example prepares a low surface energy antifouling coating with degradable properties. The only difference between this example and Example 1 is that 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is not added. Instead, 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is allocated to bis-3-aminopropyl-terminated polydimethylsiloxane according to the proportions in Example 1, and 2% diisophorone peroxide is added. The coating is cured at 150°C for 1 hour. All other aspects are the same as in Example 1.
[0063] Comparative Example 3
[0064] This comparative example prepares a low surface energy antifouling coating with degradable properties. The only difference between this example and Example 1 is that bis-3-aminopropyl-terminated polydimethylsiloxane is not added. Instead, bis-3-aminopropyl-terminated polydimethylsiloxane is distributed into 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester according to the proportions in Example 1, and 70% of the total mass of polyamide curing agent is added. The mixture is cured at 120°C for 1 hour. All other aspects are the same as in Example 1.
[0065] Test Example 1
[0066] This test case involves a biodegradability test.
[0067] The low surface energy antifouling coatings with degradable properties prepared in the above examples and comparative examples were respectively immersed in 30 mL of artificial seawater, stirred in a magnetic stirrer for 90 days, dried to remove residual moisture on the surface, and weighed again to determine the degradation performance of the coatings.
[0068] Table 1
[0069]
[0070]
[0071] The results in Table 1 above show that:
[0072] The biodegradability of the coatings was analyzed by immersing the coatings prepared in the examples and comparative examples in artificial seawater and recording the changes in mass. The degradation rate of each coating was calculated. It was found that the pure PDMS coating and the pure epoxy coating had no degradation ability because they lacked biodegradable groups. Comparing Example 1 and Comparative Example 1, epoxy E44 did not contain biodegradable groups and therefore also lacked biodegradability. Comparing Example 1 and Example 4, the coating in Example 4 was not immersed in silicone oil, and the base coating showed biodegradability, but the degradation rate was slightly lower than that of Example 1, which contained oil. This is presumably because the silicone oil on the surface of the coating in Example 1 formed "silicone oil ridges," encapsulating a portion of the artificial seawater, thus resulting in a slightly higher degradation rate. Comparing Examples 1-6, the difference between these coatings lay in the different proportions of the two raw materials added. In Examples 1-3, the ratio of the two raw materials was not significantly different, resulting in a larger proportion of reaction products and a certain degradation rate. In the other coatings, the proportions of the raw materials differed too much, and only a small portion of the products showed biodegradability, thus failing to exhibit biodegradability after thirty days of immersion in artificial seawater.
[0073] The coatings obtained in Examples 1 and 4 were observed using a scanning electron microscope. Figure 2 The test results are known, among which Figure 2 In Figure A, the coating surface of Example 4 is shown. Figure 2 B in the figure represents the cross-section of the coating in Example 4. Figure 2 C represents the coating surface of Example 1. Figure 2 Figure D shows the cross-section of the coating in Example 1. As can be seen from the figure, the coating surface is very smooth after immersion, with almost no visible pores, and the cross-section is also smooth. In contrast to the oil-free cross-section, almost all the pores are filled with oil, proving that the amount of silicone oil injected is sufficient, making the original rough surface smooth.
[0074] Test Example 2
[0075] This embodiment describes the infrared spectral characterization of the flocculent material obtained after soaking in artificial seawater.
[0076] After immersion in artificial seawater, the coating in Test Example 1 formed flocculent material. Infrared spectroscopy was performed on the flocculent material detached from the coating prepared in Example 1. The flocculent material generated by the self-degradation behavior of the coating prepared in Example 1 was filtered, dried, ground, and pressed into tablets, and its infrared spectrum was measured. Specific test results are as follows: Figure 3 As shown, 1739cm -1 The peak corresponds to C=O; 1266cm -1 The peak at 2300 cm⁻¹ corresponds to the stretching vibration of CO; -1The peak at 1468 cm⁻¹ is attributed to the stretching vibration of C=C; -1 The peak at 2925 cm⁻¹ is due to the bending vibration of -CH₃, while the peak at 2925 cm⁻¹ is due to the bending vibration of -CH₃. -1 The peak at that location originates from the strong stretching absorption of the OH group in the carboxylic acid dimer. This proves that the product of the coating's self-degradation should be 4-cyclohexene-1,2-dicarboxylic acid.
[0077] Example 3
[0078] This embodiment demonstrates the antibacterial effect of the low surface energy antifouling coatings prepared in the above embodiments and comparative examples.
[0079] To investigate the antibacterial effects of the coatings prepared in the above examples and comparative examples, *Pseudomonas aeruginosa* was used as the test subject. First, 100 μL of *Pseudomonas aeruginosa* inoculum was placed in 10 mL of Luria-Bertani (LB) broth and incubated at a constant temperature (37°C, 180 rpm) for 6 h. Then, the bacterial suspension was centrifuged, washed with 0.9% NaCl, and resuspended. The optical density (OD) value was measured using a UV spectrophotometer (10⁻¹⁰). 8 CFU mL –1 Finally, take 10 μL of bacterial culture and dilute it to 10 mL with 0.9% NaCl solution (10). 5 CFUmL –1 ).
[0080] The prepared coatings were then placed into the bacterial suspensions described above. After incubation in a shaking incubator for 24 hours, 100 μL of the prepared bacterial suspension was taken and spread onto a solid culture medium. After incubation at 37°C for 24 hours, the number of surviving colonies was determined using the plate count method.
[0081] Table 2
[0082]
[0083]
[0084] The results above show that:
[0085] Figure 4Figures A and J show images of plate colonies after incubation of blank bacterial suspension and the examples and comparative examples, respectively. The comparison shows that the pure epoxy coating has almost no antibacterial effect, while the other coatings have some antibacterial effect. Figure B shows the fewest colonies, indicating that Example 1 has the fewest colonies. Figure I shows the number of colonies after incubation of the coating in Comparative Example 2, which is 305. Due to the low surface energy of bis(3-aminopropyl)-terminated polydimethylsiloxane, bacteria adhere to the coating less than with the pure epoxy coating. Comparing Examples 1-5, it can be seen that when the epoxy group ratio is high, the coating surface cannot prevent bacterial adhesion because the epoxy groups do not have antibacterial properties, resulting in a higher colony count. Based on the results of Examples 1 and 2, i.e., Figures B and C, it can be seen that the ester groups of the biodegradable coatings in Examples 1 and 2 can effectively wash away the coating surface under water flow, inhibiting bacterial adhesion. As shown in the figures, the biodegradable low surface energy coating in Example 1 exhibits excellent antibacterial adhesion effect.
[0086] In summary, this invention utilizes the polymerization reaction of NH2-PDMS with 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester to open the epoxy group and graft the ester group onto the low surface energy siloxane side chain. Its degradability originates from the ester group in the side group, which breaks down when washed by water flow, forming a self-renewing surface and improving antifouling performance.
[0087] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A low surface energy antifouling coating with biodegradable properties, characterized in that, The structure of the low surface energy antifouling coating includes an amino group of bis(3-aminopropyl)-terminated polydimethylsiloxane linked to an epoxy group of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester. The low surface energy antifouling coating is prepared using the following method: The mixture was prepared by mixing bis(3-aminopropyl)-terminated polydimethylsiloxane and 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester and then curing the mixture. The molar ratio of the amino group of the bis(3-aminopropyl)-terminated polydimethylsiloxane to the epoxy group of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is 1:(1~5).
2. The low surface energy antifouling coating with degradable properties according to claim 1, characterized in that, The bonds that connect the molecules include ester bonds.
3. A method for preparing a low surface energy antifouling coating with degradable properties according to claim 1 or 2, characterized in that, The preparation method includes: The mixture was prepared by mixing bis(3-aminopropyl)-terminated polydimethylsiloxane and 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester and then curing the mixture. The molar ratio of the amino group of the bis(3-aminopropyl)-terminated polydimethylsiloxane to the epoxy group of 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester is 1:(1~5).
4. The method for preparing the low surface energy antifouling coating with degradable properties according to claim 3, characterized in that, The molecular weight of bis(3-aminopropyl)-terminated polydimethylsiloxane is 2500-3000.
5. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 3, characterized in that, The preparation method further includes adding solvent to the mixed raw materials and stirring, and then condensing and refluxing in an oil bath.
6. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 5, characterized in that, The solvent includes any one or a combination of at least two of tetrahydrofuran, ethyl acetate, or acetone.
7. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 5, characterized in that, The stirring time is 20-40 minutes, and the rotation speed is 100-500 rpm.
8. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 5, characterized in that, The temperature of the oil bath is 75-85℃.
9. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 5, characterized in that, The condensation reflux time is 20-24 h.
10. The method for preparing the low surface energy antifouling coating with degradable properties according to claim 3, characterized in that, The curing time is 3-7 days.
11. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 3, characterized in that, The curing temperature is 20-30℃.
12. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 3, characterized in that, The preparation method also includes immersing the cured coating in silicone oil.
13. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 12, characterized in that, The silicone oil includes any one or a combination of at least two of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, or fluorinated silicone oil.
14. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 12, characterized in that, The viscosity of the silicone oil is 5-100 mPa·s.
15. The method for preparing a low surface energy antifouling coating with degradable properties according to claim 12, characterized in that, Soaking time is 3-7 days.
16. The application of a low surface energy antifouling coating with biodegradable properties as described in claim 1 or 2 in the treatment of marine biofouling.
Citation Information
Patent Citations
Chlorine-resistant antifouling multifunctional coating for marine concrete and preparation method of chlorine-resistant antifouling multifunctional coating
CN114315417A
Composite super-lubricating coating material, preparation method thereof, composite super-lubricating coating and application of composite super-lubricating coating material
CN114539884A